2022
DOI: 10.3390/ijms23094947
|View full text |Cite
|
Sign up to set email alerts
|

Transduction of Brain Neurons in Juvenile Chum Salmon (Oncorhynchus keta) with Recombinant Adeno-Associated Hippocampal Virus Injected into the Cerebellum during Long-Term Monitoring

Abstract: Corpus cerebelli in juvenile chum salmon is a multiprojective region of the brain connected via afferent and efferent projections with the higher regions of the brainstem and synencephalon, as well as with multiprojection regions of the medulla oblongata and spinal cord. During the postembryonic development of the cerebellum in chum salmon, Oncorhynchus keta, the lateral part of the juvenile cerebellum gives rise to the caudomedial part of the definitive cerebellum, which is consistent with the data reported f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 99 publications
0
1
0
Order By: Relevance
“…Initial steps in this direction have been made through a study of juvenile Pacific salmon. In the work related to the long-term monitoring of connections between the cerebellum and other parts of the brain in juvenile chum salmon, researchers have found that recombinant adeno-associated virus (rAAV) vectors can integrate into the neurons of various regions of the brain after being injected into the cerebellum [188]. The distribution of recombinant adeno-associated viral vectors (rAAVs) after the injection of the base vector into the cerebellar tissue of juvenile chum salmon showed highly specific patterns of gene expression in bipolar neurons in the laterocaudal lobes of the tectum opticum.…”
Section: The Role Of Astroglia In the Functioning Of Neural Circuits ...mentioning
confidence: 99%
“…Initial steps in this direction have been made through a study of juvenile Pacific salmon. In the work related to the long-term monitoring of connections between the cerebellum and other parts of the brain in juvenile chum salmon, researchers have found that recombinant adeno-associated virus (rAAV) vectors can integrate into the neurons of various regions of the brain after being injected into the cerebellum [188]. The distribution of recombinant adeno-associated viral vectors (rAAVs) after the injection of the base vector into the cerebellar tissue of juvenile chum salmon showed highly specific patterns of gene expression in bipolar neurons in the laterocaudal lobes of the tectum opticum.…”
Section: The Role Of Astroglia In the Functioning Of Neural Circuits ...mentioning
confidence: 99%